2020
DOI: 10.3389/fncom.2020.00077
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Physical Obstacles on the Structural and Effective Connectivity of in silico Neuronal Circuits

Abstract: Scaffolds and patterned substrates are among the most successful strategies to dictate the connectivity between neurons in culture. Here, we used numerical simulations to investigate the capacity of physical obstacles placed on a flat substrate to shape structural connectivity, and in turn collective dynamics and effective connectivity, in biologically-realistic neuronal networks. We considered μ-sized obstacles placed in mm-sized networks. Three main obstacle shapes were explored, namely crosses, circles and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 67 publications
1
27
0
Order By: Relevance
“…In line with these experimental observations, recent numerical simulations on neuronal networks grown in patterned substrates indicate that physical obstacles or scaffolds favor the emergence of microcircuits that translate into an abundance of functional communities . The study also showed that it was not possible to directly link the arrangement of the physical obstacles with the functional traits of the network except for the extreme case in which cell positioning and connectivity were strongly dictated.…”
Section: Results and Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…In line with these experimental observations, recent numerical simulations on neuronal networks grown in patterned substrates indicate that physical obstacles or scaffolds favor the emergence of microcircuits that translate into an abundance of functional communities . The study also showed that it was not possible to directly link the arrangement of the physical obstacles with the functional traits of the network except for the extreme case in which cell positioning and connectivity were strongly dictated.…”
Section: Results and Discussionsupporting
confidence: 63%
“…In line with these experimental observations, recent numerical simulations on neuronal networks grown in patterned substrates indicate that physical obstacles or scaffolds favor the emergence of microcircuits that translate into an abundance of functional communities. 40 The study also Each configuration is an average over 4 network realizations, recorded at day 50 and containing on the order of 500 neurons. Data are shown as the mean ± standard deviation of the mean.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Causal relationships among pairs of ROIs’ activity were computed by using a modified version of Generalized Transfer Entropy (GTE) (Ludl and Soriano, 2020; Stetter et al, 2012; Tibau et al, 2020) run in Matlab. Binarized vectors for the 30 min activity trains (‘1’ for the presence of a spike, ‘0’ for absence) were constructed using a time bin of 20 ms, and an effective connection from ROI to ROI J (TE I→ J ) was established whenever the information contained in I significantly increased the capacity to predict future states of J .…”
Section: Transparent Methodsmentioning
confidence: 99%